Fatigue Damage–Resistant Physical Hydrogel Adhesion - Li, Qi; Wang, Luochang; Liu, Qihan; Hong, Wei; Yang, Canhui (Frontiers in Robotics and AI, 2021)
Strong adhesion between hydrogels and various engineering surfaces has been achieved, yet fatigue-resistant hydrogel adhesion remains challenging. Here we examine the fatigue of a specific type of hydrogel adhesion enabled by hydrogen bonds and wrinkling and show that the physical-interactions-based hydrogel adhesion can resist fatigue damage. We synthesize polyacrylamide hydrogel as the adherend and poly(acrylic acid-co-acrylamide) hydrogel as the adhesive. The adherend and the adhesive interact via hydrogen bonds. We further introduce wrinkles at the interface by biaxially prestretching and then releasing the adherends and perform butt-joint tests to probe the adhesion performance. Experimental results reveal that the samples with wrinkled interface resist fatigue damage, while the samples with flat interface fail in ~9000 cycles, at stress levels of 70% and 63% peak stresses in static failure, respectively. The endurance limit of the wrinkled-interface samples is comparable to the peak stress of the flat-interface samples. Moreover, we find that the nearly perfectly elastic polyacrylamide hydrogel also suffers fatigue damage, which limits the fatigue life of the wrinkled-interface samples. When cohesive failure ensues, the evolutions of elastic modulus of wrinkled-interface samples and hydrogel bulk, both in satisfactory agreements with the predictions of damage accumulation theory, are alike. We observe similar behaviors in different material systems with polyacrylamide hydrogels of different water contents. This work throws a sprat that physical interactions can be engaged in engineering fatigue-resistant adhesion between soft materials such as hydrogels.